Perbandingan Hukum Pidana Islam dan Hukum Nasional tentang Tindak Pidana Pemerkosaan terhadap Anak Kandung - Hidayat, Rian; HL, Rahmatiah (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2022)
This paper aims to find out the views of Islamic law and positive law on rape by the biological father and to find out the views of Islamic law and positive law on the Sungguminasa District Court Decision. The type of research used is field research or commonly referred to as Qualitative Field Research. Descriptive Qualitative Field Research is a type that describes a research as qualitative about the object being discussed in accordance with the reality that exists in society. This study uses data collection methods by Observation, Interview and Documentation. The results of this study indicate that in the view of Islam there are differences of opinion in giving punishment for fathers who rape their biological children. The first opinion states that the law is stoning, because the perpetrator is seen as a muhsan adulterer. The second opinion states that the punishment is ta‟zir, that is, the degree and type of punishment is left to the ijtihad decision of the authorities and the application of material criminal law to the crime of sexual intercourse with children in the case of decision number: 327/Pid.Sus/2020/PN. Sgm has been appropriate because has fulfilled the elements contained in 81 paragraphs (1) and (3) of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection.